Inovasi Pengelolaan Limbah untuk Pemberdayaan Masyarakat Berkelanjutan - Alghyfari, M. Raafi; Putra, Muhammad Agyf Dwi; Febriansyah, Nur Fadillah; Riano, Bobby Yusuf; Afdallah, Rahmat Edu; Rizki, Afni Alya Apipatul; Pradiani, Lutfiah Sus; Sya’bani, Agnia Nur; Rieva, Raihan Dwi; Fawalina, Vilza Avalda; Utama, Satria (Universitas Muhammadiyah Yogyakarta, 2025)
The service program conducted in Padukuhan Dayakan Kepuh, Kalurahan Dadapayu, Semanu District, Gunung Kidul Regency, focuses on community empowerment based on environmental sustainability and economic improvement through waste utilization. The main issues faced by the local community include a lack of awareness regarding environmental cleanliness, minimal innovation in waste management, and limited access to environmental education for children. The objectives of this program are to raise community awareness about the importance of maintaining environmental sustainability, encourage children's creativity in managing waste into valuable products, and optimize waste utilization as an alternative economic resource. The methods used in this program include socialization, environmental education, demonstrations, and practical training in making briquettes from corn cob waste, as well as literacy assistance for elementary school students. Additionally, supplementary programs such as the production of paving blocks from plastic waste aim to reduce plastic waste while creating an alternative eco-friendly building material. Other activities include creating village maps and installing house number stickers to facilitate location identification based on neighborhood units (RT and RW). The results of this community service show an increase in public awareness of maintaining environmental cleanliness, evidenced by active participation from residents in waste donation activities and the utilization of waste collection points. Elementary school children have demonstrated an improved understanding of waste management, reflected in their creative works during waste processing competitions. The paving block production from plastic waste has resulted in products that have the potential to be used in village infrastructure development. Overall, this program has a positive impact on enhancing environmental awareness, strengthening village identity, and opening economic opportunities based on waste utilization, thereby contributing to more sustainable village development.